HUBUNGAN ANTARA KELENGKAPAN PENGISIAN KUESIONER AUTO PSI VERBAL DENGAN KEAKURATA N PENENTUAN SEBAB DASAR KEMAT IAN DI PUSKESMAS WILAYAH SURAKARTA - Andi Suhenda (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2015)
AbstractVerbal autopsy (AV) is a new technique that is fairly representative and can be trusted to record and determinethe cause of the deaths that occurred outside of health care facilities. This study is aims to get an overviewof the completeness of filling the verbal autopsy questionnaire and the relationship of the determinationaccuracy with the main causes of death in Surakarta health centers. Analytic observation with the correlationstudy which find a relationship between the completeness fillings of the verbal autopsy questionnaire with theaccuracy of the determination of the main causes of death. The sample size is 65 people taken by multistagerandom sampling technique with a 2058 population, of the entire document of 17 health centers in the regionof the city of Surakarta. The researcher collected the data by questionnaires. Analytical analysis is using Chisquaretest. The results of the research showed that only found 52% of charging the symptoms of death wascompleted by nurses. The highest completeness is in the item description summary cause of death is filled bya doctor who will determine the cause of death. In summary item complete history of disease progression by54%, while the percentage of completeness of health care items received by patients is 66%. And there is asignificant relationship between the filling completeness of the verbal autopsy with the accuracy determinationof the cause of death.Keywords: Verbal autopsy, accuracyAbstrakAutopsi Verbal (AV) merupakan teknik baru yang cukup representatif dan dapat dipercaya untuk mencatatdan menentukan penyebab kematian yang terjadi di luar sarana pelayanan kesehatan. Penelitian ini bertujuanmendapatkan gambaran tentang kelengkapan pengisian kuesioner autopsi verbal dan hubungannya dengankeakuratan penentuan sebab utama kematian di puskesmas Surakarta. observasi analitik dengan studikorelasi yakni mencari hubungan antara kelengkapan pengisian kuesioner autopsi verbal dengan keakuratanpenentuan sebab utama kematian. Besar sampel adalah 65 orang yang diambil dengan teknik multistagerandom sampling dengan jumlah populasi 2058 dokumen dari keseluruhan 17 puskesmas di wilayah kerjaKota Surakarta. Pengumpulan data melalui kuesioner. Analisis analitik menggunakan uji Chi-square. Hasilpenelitian menunjukkan bahwa ditemukan hanya 52% pengisian gejala kematian yang diisi lengkap olehperawat. Kelengkapan tertinggi adalah pada item ringkasan keterangan sebab kematian yang diisi oleh dokteryang nantinya akan menentukan sebab kematian. Pada item ringkasan riwayat perjalanan penyakit lengkapsebanyak 54%, sedangkan persentase kelengkapan item pelayanan kesehatan yang diterima pasien sebesar66%. Dan ada hubungan yang signifikan antara kelengkapan pengisian autopsi verbal dengan keakuratanpenentuan sebab dasar kematian.Kata Kunci : Autopsi Verbal, keakuratan